Analisis Tingkat Kepuasan Mahasiswa terhadap Layanan Pengelola Program Studi Menggunakan Metode Inference Fuzzy Sugeno - Amrul Hinung Prihamayu (LPPM STIKI MALANG, 2024)
This research aims to analyze the level of student satisfaction with study program management services at the Faculty of Islamic Economics and Business (FEBI) IAIN Ponorogo using the Sugeno fuzzy inference method with the help of the Fuzzy Toolbox in the MATLAB application. The data used is primary data collected from 1036 respondents, namely active students from the Sharia Economics, Sharia Banking and Zakat and Waqf Management Study Programs. The evaluation includes five service factors: Tangible, Reliability, Responsiveness, Assurance, and Empathy, which are measured using a Likert scale. The analysis process begins with creating a fuzzy set for each variable, using the fuzzy implication function, compiling 19 fuzzy rules, and ending with defuzzification to obtain a concrete value for the level of satisfaction. The research results show that the Sugeno fuzzy method can effectively capture variations in student responses and provide accurate results regarding their level of satisfaction. This method makes it easier for the Faculty Quality Control Team team to evaluate and improve the quality of academic services, thereby making a significant contribution to continuous improvement in the management of study programs at FEBI IAIN Ponorogo.